The Influence of TKRO Workshop Practical Facilities and Infrastructure on Student Learning Outcomes - Ramdani, Maftuh Ikhsan; Supriyatna, Deddy; Putra, Ananda Yhuto Wibisono (Journal of Vocational and Career Education, 2025)
Low student learning outcomes in certain competency elements of vocational education raise concerns about the adequacy of supporting factors, particularly facilities and infrastructure. This study aims to examine the influence of workshop facilities and infrastructure in the TKRO practicum on student learning outcomes at SMK Negeri 5 Kota Serang. Using a quantitative approach with a descriptive method, data were collected from classes XI TKR 1 and XI TKR 2, totaling 73 students selected through simple random sampling. The research data passed statistical assumption tests and were further analyzed using simple linear regression, yielding an R Square value of 0.119. This indicates that workshop facilities and infrastructure contribute 11.9% to the variation in student learning outcomes. It can be concluded that although the influence is not dominant, facilities and infrastructure still significantly affect student achievement. The findings of this study are expected to serve as a reference for schools and policymakers in evaluating and improving vocational workshop facilities to enhance educational quality. Furthermore, this research highlights the importance of integrating physical resources with pedagogical practices to maximize their impact. One of the study's novel contributions is the identification of a gap between perceived adequacy of facilities and actual student performance, which emphasizes the need for better alignment between infrastructure use and instructional design. Therefore, improving learning outcomes in vocational education requires not only complete facilities but also competent teaching, motivated learners, and a structured learning environment.